PENGARUH LABELISASI HALAL, KUALITAS PRODUK, PROMOSI TERHADAP KEPUTUSAN PEMBELIAN - Aldi Alfiyan; Restu Frida Utami; Tri Septin Muji Rahayu; Meydy Fauziridwan (ITB AAS Indonesia Surakarta, 2025)
In recent years, the cosmetics business in Indonesia has experienced significant growth, characterized by an increase in cosmetics industry revenue from IDR 20 trillion in 2021 to IDR 30 trillion in 2024. The cosmetics market will be expected to grow steadily until 2027. Stable growth opens up great opportunities for scarlett whitening to continue to grow, innovate, and expand their market amid increasing consumer interest in cosmetic products. This study aims to analyze the effect of halal labeling, product quality, promotion on purchasing decisions on scarlett whitening products. This study uses a quantitative approach with purposive sampling technique. The population in this study are people who live in Purwokerto City and have purchased scarlett whitening products in the last 3 months. To obtain representative results, the researcher set a sample size of 132 respondents. The results showed that the variables of product quality and promotion had a significant effect on purchasing decisions, while the halal labeling variable had no effect on purchasing decisions. This finding indicates that although halal aspects are important to consumers, in the context of cosmetic products such as Scarlett whitening, quality and promotion factors are more dominant in influencing purchasing decisions